2020
DOI: 10.2147/cmar.s250284
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Noncoding RNA FGD5-AS1 Promotes Glioma Cell Proliferation, Migration and Invasion by Regulating wnt/β-Catenin Pathway</p>

Abstract: Purpose: To investigate the specific function of long noncoding RNA FGD5 antisense RNA 1 (lncRNA FGD5-AS1) in glioma. Materials and Methods: The level of FGD5-AS1 was detected in clinical samples and cell lines by qRT-PCR. Small interfering RNA (siRNA) of FGD5-AS1 or scramble siRNA was transfected into U87 cell lines to examine the role of FGD5-AS1 on glioma development. The proliferation of glioma cells was tested by Cell Counting Kit-8 (CCK-8), the migration and invasion of glioma cells were tested by transw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…As we reviewed the published paper, lncRNA FGD5-AS1 might serve as a prognosis factor of colon cancer, oral cancer, and melanoma (38)(39)(40)(41)(42)(43). Scholars araised interest of lncRNA FGD5-AS1 from 2018, and reported different molecular mechanism of lncRNA FGD5-AS1 in various cancer, including: regulating miR-140-5p/WEE1 axis (44), miR-153-3p/CITED2 (40), ERK/AKT signaling (45), MCL1 (42), Wnt/b-catenin (28,46), miR-103a-3p/TPD52 (47). However, the function of lncRNA FGD5-AS1 regarding breast cancer remained rarely studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we reviewed the published paper, lncRNA FGD5-AS1 might serve as a prognosis factor of colon cancer, oral cancer, and melanoma (38)(39)(40)(41)(42)(43). Scholars araised interest of lncRNA FGD5-AS1 from 2018, and reported different molecular mechanism of lncRNA FGD5-AS1 in various cancer, including: regulating miR-140-5p/WEE1 axis (44), miR-153-3p/CITED2 (40), ERK/AKT signaling (45), MCL1 (42), Wnt/b-catenin (28,46), miR-103a-3p/TPD52 (47). However, the function of lncRNA FGD5-AS1 regarding breast cancer remained rarely studied.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars reported MACC acted as an oncogene involved in cancer progress and metastasis and predicted a poor prognosis in many cancers (17)(18)(19)(20)(21)(22)(23)(24)(25). Moreover, many scholars revealed that MACC1 expression has also been associated with treatment response via interrupting Notch pathway (26), b-catenin (27,28), and HGF/cMet pathway (29). These investigations implicate MACC1 as a multifunctional regulator of cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Computational analysis also identified FGD5-AS1 as a key lncRNA for acute myocardial infarction. Other evidence of the regulatory functions of FGD5-AS1 came from studies of cancers such as colorectal cancer ( Li et al, 2019 ), non-small lung cancer ( Fan et al, 2020 ; Fu et al, 2020 ), gastric cancer ( Gao et al, 2020a ), melanoma ( Gao et al, 2020b ), oral cancer ( Liu et al, 2020 ), glioblastoma ( Su et al, 2020 ), glioma ( Lin et al, 2020 ; Zhao et al, 2020 ), renal cell carcinoma ( Yang et al, 2020 ), and hepatocellular carcinoma ( Zhang and Lou, 2020 ). A variety of related miRNAs (e.g., miR-223, miR-140-5p, miR-383, miR-153, miR-103a-3p, miR-129-5p, and miR-5590-3p) were also reported as interacting with FGD5-AS1 in the above-mentioned works.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a critical study discovered that clinical samples and cell lines had detectable quantities of FGD5 Antisense RNA 1(FGD5-AS1). By directly regulating the Wnt/-Catenin Pathway, the long non-coding RNA FGD5-AS1 promotes Glioma-related processes such as cell proliferation, migration, and invasion ( 33 ). Exosomes carrying long non-coding RNA have been reported to enhance glioma formation; for instance, recent research found that exosomes carrying Linc01060 increased glioma growth by effectively regulating the MZF1/c-Myc/HIF1 Axis ( 34 ); on the other hand, a study that examined the link between miR155HG and Annexin A2(ANXA2) to assess their malignancy in the formation of GBM discovered that the two, in combination with miR-185, enhanced glioma growth and development which proves the role of long non-coding RNA in glioma formation ( 35 ).…”
Section: Long Non-coding Rna and Glioma Developmentmentioning
confidence: 99%